Thiophene Cation Intercalation to Improve Band‐Edge Integrity in Reduced‐Dimensional Perovskites. (4th June 2020) - Ni, Chuyi; Huang, Yahao; Zeng, Tao; Chen, Daohong; Chen, Hao; Wei, Mingyang; Johnston, Andrew; Proppe, Andrew H.; Ning, Zhijun; Sargent, Edward H.; Hu, Peng; Yang, Zhenyu
Abstract: The insertion of large organic cations in metal halide perovskites with reduced‐dimensional (RD) crystal structures increases crystal formation energy and regulates the growth orientation of the inorganic domains. However, the power conversion performance is curtailed by the insulating nature of the bulky cations. Now a series of RD perovskites with 2‐thiophenmethylammonium (TMA) as the intercalating cation are investigated. Compared with traditional ligands, TMA demonstrates improved electron transfer in the inorganic framework. TMA modifies the near‐band‐edge integrity of the RD perovskite, improving hole transport. A power conversion efficiency of 19 % is achieved, the highest to date for TMA‐based RD perovskite photovoltaics; these TMA devices provide a 12 % relative increase in PCE compared to control RD perovskite devices that use PEA as the intercalating ligand, a result of the improved charge transfer from the inorganic layer to the organic ligands. Abstract : Giving perovskite the edge : The influence of intercalating ligands on crystal and electronic structures of reduced‐dimensional (RD) perovskite has been investigated. A destabilized aromatic group, such as thiophene, effectively tailors the band‐edge electronic states and improves charge carrier mobilities. RD perovskite photovoltaics with thiophene‐based ligands show improved performance compared to devices using conventional intercalating cations.